Prevalence of Tigecycline resistance in Multidrug-Resistant Acinetobacter species isolates from clinical specimens - Mahto, Moni; Dhungel, Banodita Acharya (Janaki Medical College Journal of Medical Science, 2019)
Background and Objectives: Acinetobacter baumanii is ubiquitous, aerobic non fermentative, gram negative cocobacilli, emerging globally as an important cause of nosocomial infection. This study was conducted to determine the prevalence and antibiogram of clinically isolated multidrug-resistant Acinetobacter species. Material and methods: Antibiotic susceptibility of 93 Acinetobacter baumannii isolates were performed against ampicillin, ampicillin/sulbactam, piperacillin/tazobactam, ceftazidime, cefepime, ceftriaxone, cefotaxime, ciprofloxacin, levofloxacin, amikacin, gentamicin, imipenem, meropenem, tigecycline, polymyxin B and colistin as per standard methods in microbiology laboratory of Nepal Mediciti Hospital, Kathmandu, Nepal from January to December 2018. Ethical clearance was taken from the Institutional review committee of Nepal Mediciti Hospital. Results: A total of 93 Acinetobacter baumannii isolates were obtained from sputum, blood, pus, wound swabs , catheter tips and others. Antibiotic susceptibility analyses of the isolates revealed that the resistance to ampicillin was most common (100%), followed by cefotaxime (75.2%), ceftazidime (74.1%), ampicillin/sulbactam (73.1%), cefepime (67.7%). However, almost all isolates were susceptible to tigecycline (100%), followed by colistin (98.9%), and polymyxin B (87.0%). Conclusion: The present study showed the increasing trends of resistance of Acinetobacter speciesto various classes of antimicrobials. Treatment options for infections due to MDR and XDR Acinetobacter baumanii are very limited and tigecycline and colistin may be considered as one of the therapeutic option for the treatment of hospital acquired infections